“Interview” and (auto)biography. Cultural-historical and media contexts of a newspaper column - Stoichkova, Noemi; Stoyanova, Nadezhda (Літературний процес: методологія, імена, тенденції, 2020)
The article aims to present and analyse the cultural-historical and media contexts of the column “An Hour at…” from the Bulgarian newspaper of the 1930s — Literary Voice. The methods of cultural and literary-historical study are used. It is concluded that, by integrating the genres of interview and (auto)biography, this column has rehabilitated the role of the European intellectual after the crisis of the 1920s. The article is a part of a larger study.